Effect of conscious pronation on oxygen saturation in patients hospitalized for COVID-19 - Chambi, Liliana (2021)
Objective: to determine the effect of conscious pronation on oxygen saturation in patients hospitalized for COVID-19. Methods: the present study was analytical - cross-sectional. The population was made up of patients hospitalized in one of the wards for COVID-19 at the Hospital Nacional Hipólito Unánue during the period June to August 2020. A consecutive convenience sampling of all patients included in the period of study. Hospitalized patients older than 18 years were included, with the diagnosis of COVID-19 by serological and molecular tests.Those with some degree of encephalopathy, post-operated, pregnant, patients with hemodynamic instability were excluded. The mean arterial oxygen saturation (SaO2) baseline was compared with that obtained after one and two hours of pronation. Likewise, the factors associated with the change in saturation were evaluated. Results: of the 198 hospitalized patients, 144 were men, 31,8% were older than 65 years and 30,3% were younger than 49 years. Hypertension was present in 62,6%, being the most common comorbidity followed by diabetes mellitus and obesity. The mean SaO2 before pronation was 89,4 ± 0,24, increasing significantly (p <0,001) one hour after pronation to 95,6 ± 0,30. At two hours, the mean saturation increased to 96,7 ± 0,30 (p <0,001). In multivariate analysis, a history of tuberculosis, a higher lymphocyte and platelet count were significantly associated with a better response to pronation, while urea levels were associated with a lower response. Conclusion: conscious pronation is associated with significant improvements in oxygen saturation after one and two hours after the intervention.This intervention should be included in the hospital care protocols for patients with severe pneumonia associated with COVID-19.